EFFECTIVENESS OF ANTIHELMINTIC MEDICINES IN THE TREATMENT OF FASCIOLYSIS IN GOATS IN THE CONDITIONS OF SURKHANDARDO REGION (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The prevalence, extensiveness, and intensity of fascioliasis among goats in the Surkhandarya region have been determined